Computational studies on shape memory polymer under various deformations - Sujithra, R.; Srinivasan, S. M.; Arockiarajan, A. (Journal of Structural Engineering, 2024)
Shape memory polymers (SMP) have increased attention for numerous applications ranging from biomedical to aerospace industry. These applications involve tension, compression and bending loads. To analyze the behavior of shape memory polymer under thermomechanical loading cycle, a simple framework is presented here. It focuses on modeling the two unique features of SMP namely temperature and deformation dependent change in the stiffness and the shape memorizing characteristics. This framework is incorporated into commercial FE solver like ABAQUS coupled with user material (VUMAT) subroutine for numerical simulation. The primary objective in this paper is tostudy the shape storage and recovery cycle of this polymer under tension, compression and bending deformation.